Actuotaphonomic of fish microteeth accumulations in intertidal environments: a case study in Atalaia Beach, Northeast Amazon, Brazil. (Brazilian Geographical Journal, 2013)
A study of fish microteeth accumulations in the intertidal environment was carried out in Atalaia Beach, northeast Amazon, Brazil, from the analysis of 18 samples of recent sediments taken from 50cm holes. No specimens were found in the material, a result influenced by factors arising from the very nature of the area, such as Beach dynamics, temperature and shallow water depth. However, this result resembles the one found in intertidal Miocene deposits of the same region, reinforcing the use of current taphonomy as a support tool for paleoecological studies. Key Words: Intertidal, Accumulations, Microteeth.